Causes of Hospital Violence, Characteristics of Perpetrators, and Prevention and Control Measures: A Case Analysis of 341 Serious Hospital Violence Incidents in China - Ma, Yuanshuo; Wang, Licheng; Wang, Yongchen; Li, Zhe; Zhang, Yafeng; Fan, Lihua; Ni, Xin (Frontiers in Public Health, 2022)
Abstract Objective: Hospital violence remains a global public health problem. This study aims to analyze serious hospital violence causes in China and the characteristics of perpetrators. It likewise seeks to understand frontline personnel’s needs and put forward targeted suggestions. Methods: Serious hospital violence cases from 2011 to 2020 in the China Judgment Online System (CJOS) were selected for descriptive statistical analysis. A total of 72 doctors, nurses, hospital managers, and security personnel from 20 secondary and tertiary hospitals in China were selected for semi-structured interviews. Results: Of the incidents, 62.17% were caused by patients’ deaths and dissatisfaction with their treatment results. Moreover, it was found that out-of-hospital disputes (11.14%) were also one of the main reasons for serious hospital violence. The perpetrators were mainly males (80.3%), and had attained junior high school education or lower (86.5%). Furthermore, most of them were family members of the patients (76.1%). Healthcare workers urgently hope that relevant parties will take new measures in terms of legislation, security, and dispute handling capacity. Conclusion: In the past 10 years, serious hospital violence’s frequency in China has remained high. Furthermore, their harmful consequences are more serious. The causes of hospital violence are diverse, and the characteristics of perpetrators are obvious. Frontline healthcare workers urgently need relevant parties to take effective measures in terms of legislation, security, and dispute handling capacity, to prevent the occurrence of violence and protect medical personnel’s safety.